Nanostructured Ni-B Seed Layer Electrocatalysts for Oxygen Evolution Reaction - Morshedlo, Taghi; Hosseini, Seyed Alireza; Shahini, Mohammad Hossein; Ghorbanzadeh, Soghra; Alishahi, Mostafa (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
The current study investigates the electrocatalytic activity of the nanostructured Ni-B seed layer deposited on carbon paper for the oxygen evolution reaction. Accordingly, the influence of several fabrication parameters and post-heat treatment on the electrocatalytic behavior of the samples is studied. Nanostructure seed Ni-B/CP electrodes were synthesized by an electroless deposition method, and a uniform layer of nanostructure seeds was obtained after 120 s of deposition time. Results have shown by the rising B content the catalytic properties of the Ni-B/CP electrodes are enhanced. The catalytic activity for OER diminished after heat treatment at 400 ºC for 1 h. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).